A taxonomic revision of the Palaearctic species of the ant genus Tapinoma Mayr 1861 (Hymenoptera: Formicidae) - Seifert, Bernhard; Kaufmann, Bernard; Fraysse, Lorenzo (Zootaxa, 2024)
A taxonomic revision of the Palaearctic species of the ant genus Tapinoma Emery 1861 is provided. Due to the extreme rarity of discernable characters, the female castes of 64% of the species are not separable by primary visual perception of an expert and are thus truly cryptic. The main working rationale of the revision is Numeric Morphology-Based Alpha-Taxonomy (NUMOBAT) with formation of species hypotheses largely based on exploratory data analyses and checking these hypotheses by discriminant analysis. NUMOBAT data of all considered species comprise 648 worker samples with 2014 individuals and 30,000 primary data. Species are depicted by z-stack imaging in three standard visual positions. Numeric data on 15 phenotypical characters are presented in comparative tables and supplementary verbal descriptions are given. Analysis of nuclear DNA was based on evaluation of 15 microsatellite loci in 274 nest samples. The NUMOBAT-based classification of eight species of the Tapinoma nigerrimum and T. simrothi group which are inseparable by subjective visual inspection was confirmed by nuclear DNA data in 98.3% of 169 samples where both morphological and nuDNA data were available. The three cases of disagreement between NUMOBAT and nuDNA classification were discussed. Excluding Nomina Nuda and unavailable names, the revision recognized 34 available names which divide into 21 valid species, 11 junior synonyms and two names placed under Incertae Sedis. Four species are described as new: Tapinoma hispanicum n. sp., T. insularis n. sp., T. dabashanica n. sp. and T. sichuense n. sp. The following synonymies were stated: T. collina Foerster 1850, T. erraticum platyops Emery 1925 and T. erraticum bononiensis Emery 1925 as synonyms of T. erraticum (Latreille 1798); T. tauridis Emery 1925 and T. breve Emery 1925 as synonyms of T. glabrella (Nylander 1849) that is erected to species level; T. minor Bernard 1945 as synonym of T. simrothi Krausse-Heldrungen 1911; T. simrothi azerbaidzhanica Karavajev 1932 as synonym of Tapinoma karavaievi Emery 1925 that is erected here to species level; T. erraticum ambiguum Emery 1925 as synonym of T. madeirense Forel 1895 and T. emeryanum Kuznetzov-Ugamsky 1927 as synonym of T. sinense Emery 1925. Despite an insufficient separation of the female castes of Tapinoma madeirense and T. subboreale Seifert 2011 by NUMOBAT characters and detection of a hybrid zone in southern France, the heterospecific status of the two taxa was maintained based on sufficient differences in male genitalia and of nuclear DNA over a larger geographic scale. Formica caerulescens Losana 1834 is removed from genus Tapinoma and recognized as member of the subfamily Formicinae.